Nutrition Education for Pregnant Women to Improve the Nutritional Status of Mothers and Fetuses - Inna Noor Inayati; Anita Lontaan (Bulletin of Inspiring Developments and Achievements in Midwifery, 2025)
The nutritional status of pregnant women is a major determinant of maternal and fetal health. Not only malnutrition such as anemia and chronic energy deficiency (CED), but also excess nutrition such as obesity can cause pregnancy complications. However, most nutritional interventions have not considered variations in nutritional status based on maternal body mass index (BMI). Nutrition education is one of the important interventions bto improve knowledge and change nutritional consumption behavior. This study aims to evaluate the effectiveness of nutritional education on the nutritional status of pregnant women and their fetuses. The study used a pre-post test design with a quantitative approach on 60 pregnant women in the second trimester who received nutrition education for 4 weeks. The parameters measured were changes in hemoglobin levels, upper arm circumference (MUAC), and weight gain. The results showed a significant increase in the average hemoglobin level (p <0.05) and MUAC after the intervention. Nutrition education has been proven effective in improving the nutritional status of pregnant women, both in terms of anemia, energy, and weight. This intervention should be an integral part of antenatal care (ANC) services, taking into account the diversity of maternal nutritional status and socio-economic background.